Living and Studying in the US: An Ecological Systems Perspective - Simone C Conceiçao; Liliana Mina; Todd Southern (Adult Education Research Conference, 2018)
International students encounter many issues when living and studying in the United States. It is essential to understand how these adult students make meaning of these experiences. The purpose of this study was to gain insights into the meaning of the lived experiences of international students living and studying in the U.S. six months after returning to their home country. Phenomenology was the research approach used to explore participants’ perspectives of their lived experiences. Findings show how the interactions between participants’ development and the multiple systems they lived through influenced their experiences and perspectives and contributed to their identity development. Findings show the need for adult educators to be aware of the challenges and opportunities international students encounter and provide support to encourage growth and development.
Keywords: ecological systems theory; identity development; international students; perspective transformation